South African Public opinion on Government's performance in the area of School Education in Post-Apartheid South Africa - Richmond, Samantha (Department of Political Studies, 2014)
The aim of this research project is to empirically unpack South African public opinion on government's performance in the area of school education. The descriptive analysis chapter shows that school education has not been as politically salient an issue amongst South Africans in post-apartheid South Africa. In addition, this chapter also shows that a vast majority of South Africans positively evaluate government's performance in the area of school education. Furthermore, the multivariate analysis chapter shows that the significant demographic variables collectively formed the strongest basis on which South Africans evaluated government's performance, followed by the significant general experiences with education variable and the significant heuristics variables respectively. Moreover, South Africans' perceptions of the present versus the past appear to be the strongest individual determinant of government's performance. The evidence therefore suggests that South Africans are making use of a schema that deals with their experiences of school education under apartheid to evaluate government's performance.